Bed-knob and broomstick - Norton, Mary (Harcourt, 2000)
With the powers they acquire from a spinster who is studying to be a witch, three English children have a series of exciting and perilous adventures traveling on a flying bed that takes them to a London police station, a tropical island, and back in time to the seventeenth century.